PENGARUH RESPONSIBILITAS, EMPATI, RELIABILITAS PENGURUS TERHADAP LOYALITAS ANGGOTA KOPERASI BUMI KRESNA - Yunus . (Holistik Manajemen: Jurnal Manajemen, 2021)
The Bumi Kresna Cooperative Management as the manager in charge of providing services to members of the Bumi Kresna Cooperative in running the cooperative's economy. Services provided by the management so far are still less responsive to the needs of consumer goods and clothing needed by members. The empathy that is carried out by the management is often an obstacle and becomes a talk among members. The reliability of the management in routine service activities is often not according to the appointments or schedules. The ability to provide services that are not up to standard will have an impact on members in conducting transactions, reducing loyalty as customers which results in problematic member loyalty. This research is focused on the Effect of responsibility, empathy, management reliability on loyalty of the Kresna Bumi cooperative members", while the aim of the study is to increase knowledge related to the effect of responsibility, empathy, and reliability of the Kresna Bumi management on members’ loyalty. within the Police Intelligence and Security Center, proving the influence of the responsibility of the Kresna Bumi cooperative management on the loyalty of members of the Kresna Bumi Koperasi, proving the influence of empathy of the Bumi Kresna Cooperative administrators on the loyalty of members of the Kresna Bumi Cooperative, and proving the effect of the reliability of the Bumi Kresna Cooperative management on the loyalty of members of the Kresna Bumi Cooperative. The results showed that the responsibility, empathy, and reliability of the Bumi Kresna Cooperative management together have a positive effect on the loyalty of the members of the Kresna Bumi Cooperative who are in the Pusdik Intelkam environment. The management responsibility variable has a positive effect on member loyalty, the management empathy variable has a positive effect on the loyalty of members of the Bumi Kresna Cooperative, and the management reliability variable has a positive effect on the loyalty of the Kresna Bumi Koperasi members. Keywords ; Responsibility, Empathy, Reliability and Loyalty.